Next-generation rheumatoid factor assay provides improved predictive power for the development of arthritis in patients at risk - Gertjan Wolbink; Theo Rispens; Dirkjan van Schaardenburg; Laurette van Boheemen; Pleuni Ooijevaar-De Heer; Nienke Oskam; Dorien Kos (RMD Open)
Objective Rheumatoid arthritis (RA) is characterised by the presence of autoantibodies, among which those targeting the constant region of immunoglobulin G (IgG), called rheumatoid factors (RF). Despite this link, RFs can also be found in other disorders and the healthy population, which hampers its use as a diagnostic tool. We recently showed that a subset of RA-derived RFs target a distinct epitope on the IgG-Fc, a feature that is currently not used in the clinic.Methods We determined immunoglobulin M (IgM)-RF levels specific against an RA-associated epitope (using our engineered next-generation RF antigen ‘T3-17’) in a prospective cohort of 475 patients with seropositive (for IgM-RF or aCCP) arthralgia that were followed for 5 years or until the development of arthritis.Results The presence of RFs targeting T3-17 was more strongly associated with progression to arthritis in comparison to traditional RF measurements. Within the group of patients positive for T3-17 RF the risk of arthritis development was increased as compared with wild-type RF, HR=3.2 (95% CI 2.4 to 4.3) vs HR=2.2 (95% CI 1.7 to 3.0). Predictive power of T3-17 RF was improved in combination with aCCP titres, HR=6.4 (4.7–8.7) vs HR=5.1 (3.9–6.8). This combination performed better than aCCP detection on its own.Conclusion The detection of disease-specific RF is feasible and seems to improve the diagnostic power of RF and should be considered to be implemented in the clinic.